2016
DOI: 10.1093/jac/dkw322
|View full text |Cite
|
Sign up to set email alerts
|

Safety, clinical effectiveness and trough plasma concentrations of intravenous posaconazole in patients with haematological malignancies and/or undergoing allogeneic haematopoietic stem cell transplantation: off-trial experience

Abstract: This non-clinical trial experience suggests that iv posaconazole appeared to be safe and clinically effective for prophylaxis or treatment of IFD in patients receiving treatment for haematological malignancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 43 publications
3
11
0
1
Order By: Relevance
“…Our data demonstrates stable median posaconazole serum levels at steady-state of 1,067 mg/L (IQR 574-1,498 mg/L) for antifungal prophylaxis and 904 mg/L (IQR 728-1,550 mg/L) for antifungal therapy. These results are in line with several studies in patients with hematological/oncological underlying diseases reaching these targeted exposure ranges (Cornely et al, 2016;Cumpston et al, 2015;Jeong et al, 2016;Pham et al, 2016). Nevertheless, the rate of patients who achieved the targeted posaconazole serum levels at steady state is comparable to a study by Miceli et al (2015), but lower compared to other published data (Durani et al, 2015;Liebenstein et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…Our data demonstrates stable median posaconazole serum levels at steady-state of 1,067 mg/L (IQR 574-1,498 mg/L) for antifungal prophylaxis and 904 mg/L (IQR 728-1,550 mg/L) for antifungal therapy. These results are in line with several studies in patients with hematological/oncological underlying diseases reaching these targeted exposure ranges (Cornely et al, 2016;Cumpston et al, 2015;Jeong et al, 2016;Pham et al, 2016). Nevertheless, the rate of patients who achieved the targeted posaconazole serum levels at steady state is comparable to a study by Miceli et al (2015), but lower compared to other published data (Durani et al, 2015;Liebenstein et al, 2018).…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, our study demonstrates only a small number of adverse drug reactions rated as at least possibly associated with novel posaconazole formulations, which is comparable to other published data (Belling et al, 2017;Jeong et al, 2016;Kim et al, 2016). However, a study by Pham et al reported a relatively high rate of hepatotoxity of >10% of the observed patient population who received posaconazole tablet for prophylaxis and therapy of IFDs (Pham et al, 2016).…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations